Stability analysis of internal dragline dump: Distinct modeling - Kumar T.; Garg P.; Rai R.; Shrivastva B.K. (My University, 2025)
The stability of mine waste dump is of vital importance from economic and safety point of view. The internal dumps are composed of a mixture of fragmented rocks and loose soil. Their characteristic is comparable to heavily discontinuous solid mass. The present paper deals with the stability analysis of an internal dragline dump of an opencast coal mine by discrete element method. The discontinuum modelling considerer the discrete nature of the geo-materials found in external overburden dump. The discrete element method uses a circular disk to represent the granular solid mass and their interactions are described by the Newton’s third law of motion. The location of crack has been determine and found in the base of the coal rib. The stable slope angle has been determined for present case and width of coal has been varied to understand their effect on stability of dump slope. © ÖGG